Institutions with a language-critical agenda in the UK - Busse, Beatrix (Handbuch europäische Sprachkritik online, 2019)
Since its beginning in the 15th century, the standardisation of English in Britain has largely been carried out without governmental control. Thus, there has never been any language institution comparable to the Italian Accademia della Crusca and the Académie Française in Britain, despite several attempts at establishing one in the 17th and 18th century. Nevertheless, the cultivation and codification of the English language was supported by a number of influential academic societies. The general tradition in Britain is, however, largely in favour of descriptivism rather than prescriptivism of language norms, even though individuals and societies voicing prescriptive attitudes have always been present. The ability for expressing oneself in “correct” English if the situation requires it thus remains to be of high social significance.
Gesehen am 30.06.2020